2015
DOI: 10.1038/srep14390
|View full text |Cite
|
Sign up to set email alerts
|

The role of putrescine in the regulation of proteins and fatty acids of thylakoid membranes under salt stress

Abstract: Polyamines can alleviate the inhibitory effects of salinity on plant growth by regulating photosynthetic efficiency. However, little information is available to explain the specific mechanisms underlying the contribution of polyamines to salt tolerance of the photosynthetic apparatus. Here, we investigated the role of putrescine (Put) on the photosynthetic apparatus of cucumber seedlings under salt stress. We found that NaCl stress resulted in severe ion toxicity and oxidative stress in cucumber chloroplasts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 53 publications
(72 reference statements)
5
64
0
2
Order By: Relevance
“…Putrescine has been shown to be involved in plant response to abiotic tresses, such as mineral deficiency in Hordeum vulgare (Smith, ), osmotic shock in barley, corn, wheat, and wild oat (Flores and Galston, ), low pH and potassium deficiency in oat (Young and Galston, , ), salt stress in cucumber (Shu et al ., ), and cold stress in cucumber, chickpea, Arabidopsis (Shen et al ., ; Nayyar and Chander, ; Cuevas et al ., ). Putrescine is supposed to improve membrane stability under stress conditions (Farooq et al ., ; Benavides et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Putrescine has been shown to be involved in plant response to abiotic tresses, such as mineral deficiency in Hordeum vulgare (Smith, ), osmotic shock in barley, corn, wheat, and wild oat (Flores and Galston, ), low pH and potassium deficiency in oat (Young and Galston, , ), salt stress in cucumber (Shu et al ., ), and cold stress in cucumber, chickpea, Arabidopsis (Shen et al ., ; Nayyar and Chander, ; Cuevas et al ., ). Putrescine is supposed to improve membrane stability under stress conditions (Farooq et al ., ; Benavides et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Shu et al . () revealed that putrescine was implicated in altered unsaturated fatty acid content and alleviated damage to thylakoid membranes, in addition to stabilizing photosynthetic apparatus under salt stress. It is also demonstrated that putrescine plays a role in maintaining ROS homeostasis by regulating the antioxidant system to elevate abiotic stress tolerance (Liu et al ., ; Wang et al ., ; Song et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Koc (2015) also reported the negative impacts of plant growth promoting bacteria and arbuscular mycorrhizal fungi on lipid peroxidation and total phenolics of strawberry when grown under stress condition. The exogenous application of SA and Put reduced the lipid peroxidation as compared to stress control (Sun et al 2013;Shu et al 2015). Noteworthy, the synergistic effect of PGR and PGPR was more pronounced.…”
Section: Discussionmentioning
confidence: 99%
“…It was inferred that PAs acted as an antioxidant machinery to counteract oxidative stress produced under heat and drought stress. However, out of the three main polyamines (Put, Spd and Spm), Put seems to play a central role in stress tolerance due to its higher content and thus scavenges ROS leading to reduced oxidative damage as also observed by Shu et al (2015) under salt stress. It is generally believed that higher PAs can bind strongly to the negative charges in cellular components such as proteins and phospholipids and thereby stabilize the membranes under stress conditions (Asthir et al 2004;Liu et al 2007).…”
Section: Discussionmentioning
confidence: 99%